Experiencing health‐related quality of life in paediatric short stature – a cross‐cultural analysis of statements from patients and parents. (4th July 2017) - Sommer, Rachel; Bullinger, Monika; Chaplin, John; Do, Ju‐ky; Power, Mick; Pleil, Andreas; Quitmann, Julia
Abstract : Objectives: Direct assessment of the patient perspective is necessary to thoroughly understand patients' experiences of disease. We aimed to examine information from children with short stature on their perceived HrQoL within 5 European countries. Methods: Patients, identified through clinical databases, were approached by their clinicians according to the inclusion criteria regarding a diagnosis of growth hormone deficiency or idiopathic short stature and age requirements. A focus group methodology was applied in 84 children and 112 parents. Based on a category system, individual statements were allocated to domains. To evaluate the emerging topics, qualitative content analysis was conducted. Domains and respective coding frequencies per category were compared across countries and respondents. Results: The highest number of statements produced by the children and parents were related to social (29%) and emotional needs and concerns (28%). In particular, children stressed their experience of social exclusion but also their perception of social support. Regarding emotional needs, they stated mainly the desire to be taller in order to be less teased by peers. National differences were identified, for example, Swedish (22%) and British (16%) children and their parents (Sweden 26%; Britain 23%) stressed physical HrQoL aspects, whereas German children (21%) strongly focused on treatment aspects, mainly the benefit of treatment. Conclusion: Comprehensive knowledge of the impact of a chronic condition such as short stature on wellbeing is an important precondition of effective treatment. Because socioemotional topics were rated in all the countries to be most important, interventions aimed at improving HrQoL should target social and emotional responses to short stature.